2017
DOI: 10.3892/ijo.2017.4016
|View full text |Cite
|
Sign up to set email alerts
|

High miR-122 expression promotes malignant phenotypes in ccRCC by targeting occludin

Abstract: Renal cell carcinoma (RCC) is the most common neoplasm of the adult kidney, and clear cell RCC (ccRCC) represents its most common histological subtype. Although several studies have reported high expression of miR-122 in ccRCC, its physiological role remains unclear. To clarify the role of miR-122 in ccRCC, we compared miR-122 expression levels in non-cancerous tissue and ccRCC. Significant upregulation of miR-122 was observed in ccRCC specimens. Moreover, ccRCC patients with high miR-122 expression showed poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Fan, Y et al have indicated that miR-122 contributed to metastasis of ccRCC by regulating Dicer [27]. Furthermore, high level expression of miR-122 promoted malignant phenotypes in ccRCC [28]. The changing roles of miR-122 might result from sophisticated interactions in diverse tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Fan, Y et al have indicated that miR-122 contributed to metastasis of ccRCC by regulating Dicer [27]. Furthermore, high level expression of miR-122 promoted malignant phenotypes in ccRCC [28]. The changing roles of miR-122 might result from sophisticated interactions in diverse tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ccRCC is highly invasive, nearly 60% patients present metastasis at the procedure of diagnosis and therapy [19] . Meanwhile, metastatic cancer is not sensitive to chemotherapy and radiotherapy [20] . So, 5-year survival rate of ccRCC becomes negative and is of great significance to the therapeutic effect of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNAs, including miR-138 [13], miR-122 [32], miR-101 [33], miR-206 [34], and miR-429 [35], have been dysregulated and play an important role in crucial cellular biological processes in ccRCC, including cell proliferation, migration, and invasion, as well as apoptosis. In the present study, we found that miR-146a was up-regulated in ccRCC tissues compared with the adjacent non-tumor tissue.…”
Section: Discussionmentioning
confidence: 99%